Review of Eleonora Naxidou, Η ευρωπαϊκότητα εντός της βουλγαρικής βαλκανικότητας: Ο Λιούμπεν Καραβέλοφ, ο φεντεραλισμός και οι Έλληνες: [Europeanness in the context of Bulgarian Balkanness: Ljuben Karavelov, federalism and the Greeks] - Litina, Maria (Historein, 2025)
Review of Eleonora Naxidou, Η ευρωπαϊκότητα εντός της βουλγαρικής βαλκανικότητας: Ο Λιούμπεν Καραβέλοφ, ο φεντεραλισμός και οι Έλληνες [Europeanness in the context of Bulgarian Balkanness: Ljuben Karavelov, federalism and the Greeks]. Athens: Alexandria, 2021. 311 pp.